2011
DOI: 10.1016/j.neuroscience.2011.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous growth hormone attenuates cognitive deficits induced by intermittent hypoxia in rats

Abstract: Sleep disordered breathing (SDB), which is characterized by intermittent hypoxia (IH) during sleep, causes substantial cardiovascular and neurocognitive complications and has become a growing public health problem. SDB is associated with suppression of growth hormone (GH) secretion, the latter being integrally involved in the growth, development and function of the central nervous system (CNS). Since GH treatment is able to attenuate neurocognitive deficits in a hypoxic-ischemic stroke model, GH, GH receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 73 publications
2
64
0
1
Order By: Relevance
“…Further studies indicated that GH may improve spinal cord conduction and attenuate edema formation and cell injury in the spinal cord provided additional support for a beneficial role of the hormone in injuries to the cord [8,71]. In rats exposed to chronic sustained hypoxia injection of GH increased the hippocampal expression of the IGF-1 gene transcript, reduced the hypoxia-induced hippocampal injury and attenuated hypoxia-induced cognitive deficits [72]. The investigators behind this study concluded that exogenous GH may provide a viable therapeutic intervention to protect hypoxia-vulnerable brain regions from neuronal damage and subsequent deficits in neuro cognitive function.…”
Section: Gh and Neuroprotectionmentioning
confidence: 93%
“…Further studies indicated that GH may improve spinal cord conduction and attenuate edema formation and cell injury in the spinal cord provided additional support for a beneficial role of the hormone in injuries to the cord [8,71]. In rats exposed to chronic sustained hypoxia injection of GH increased the hippocampal expression of the IGF-1 gene transcript, reduced the hypoxia-induced hippocampal injury and attenuated hypoxia-induced cognitive deficits [72]. The investigators behind this study concluded that exogenous GH may provide a viable therapeutic intervention to protect hypoxia-vulnerable brain regions from neuronal damage and subsequent deficits in neuro cognitive function.…”
Section: Gh and Neuroprotectionmentioning
confidence: 93%
“…Canessa et al (2011) reported deficits in short-and long-term memories associated with focal reductions in gray matter volume in hippocampus, parietal cortex, and superior frontal gyrus in patients with severe obstructive sleep apnea. Deficits in spatial working memory in water maze protocol were observed in rodents exposed to intermittent hypoxia (Li et al, 2011). However, it has been suggested that a minimum amount of exposition to intermittent hypoxia is necessary to cause detectable memory impairments (Ward et al, 2009).…”
Section: Bres : 43956mentioning
confidence: 99%
“…The rhGH treatment in the present study increased the IGF1 gene expression in hippocampus compared with the AAS-treated animals. In alignment with this is a recent demonstration of increased hippocampal Igf1 gene expression in pituitary-intact animals, after GH treatment (Li et al 2011b). Since hippocampus represents a brain area essential for learning and memory it is tempting to suggest that an upregulation of the Igf1 gene transcript in the hippocampus may be associated with improved spatial behavior as seen in the rhGHtreated animals.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, GH was shown to counteract apoptosis induced by morphine treatment in cells derived from the mouse hippocampus (Svensson et al 2008) and studies have further demonstrated that the hormone may promote neuroprotection (Nyberg & Sharma 2002, Aberg et al 2006. Impairments of spatial learning and memory have also been seen in GH-deficient spontaneous dwarf rats (Li et al 2011a), and in a model with hypoxia GH was able to attenuate deficits in spatial learning (Li et al 2011b). We have recently demonstrated that GH may improve spatial performance in hypophysectomized rats using the Morris water maze (MWM; Le Grevès et al 2006) as well as the radial arm maze (Le Grevès et al 2011).…”
Section: Introductionmentioning
confidence: 99%